The Existence of a Class of Balanced Multi‐output Rotation Symmetric Boolean Functions. Issue 5 (1st September 2018) - Du, Jiao; Fu, Shaojing; Qu, Longjiang; Li, Chao; Pang, Shanqi
Abstract : A new characterization of balanced rotation symmetric ( n, m )‐functions is presented. Based on the characterization, the nonexistence of balanced rotation symmetric ( p r, m )‐functions is determined, where p is an odd prime and m ≥ 2. And there exist balanced rotation symmetric (2 r, m )‐functions for 2 ≤ m ≤ 2 r − r . With the help of these results, we also prove that there exist rotation symmetric resilient (2 r, m )‐functions for 2 ≤ m ≤ 2 r − r − 1.